Interface Flux Recovery coupling method for the ocean–atmosphere system - K. Chad Sockwell (Results in Applied Mathematics, 2020)
Component coupling is a crucial part of climate models, such as DOE’s E3SM (Caldwell et al., 2019). A common coupling strategy in climate models is for their components to exchange flux data from the previous time-step. This approach effectively performs a single step of an iterative solution method for the monolithic coupled system, which may lead to instabilities and loss of accuracy. In this paper we formulate an Interface-Flux-Recovery (IFR) coupling method which improves upon the conventional coupling techniques in climate models. IFR starts from a monolithic formulation of the coupled discrete problem and then uses a Schur complement to obtain an accurate approximation of the flux across the interface between the model components. This decouples the individual components and allows one to solve them independently by using schemes that are optimized for each component. To demonstrate the feasibility of the method, we apply IFR to a simplified ocean–atmosphere model for heat-exchange coupled through the so-called bulk condition, common in ocean–atmosphere systems. We then solve this model on matching and non-matching grids to estimate numerically the convergence rates of the IFR coupling scheme.